Enhancing Questioning Skills in Preschool Children with Speech Delays Through Project-Based Learning - Nursari, Amelia; Sukinah, Sukinah (Papanda Publisher, 2025)
Speech delays affect 5-10% of preschool children and significantly impact questioning skill development, which is essential for cognitive growth and academic success. This study investigated the effectiveness of project-based learning in enhancing questioning competencies among kindergarten children with speech delays. A classroom action research design following Kemmis and McTaggart's spiral model was implemented across three intervention cycles with two kindergarten students (aged 4-6 years) diagnosed with speech delays in East Kalimantan, Indonesia. Data collection employed structured observation rubrics assessing questioning behaviors across four dimensions: question initiation frequency, complexity, contextual appropriateness, and verbal clarity. Project-based learning activities focused on environmental exploration and geometric shape identification through collaborative maket construction. Quantitative analysis examined pre-post score comparisons, while qualitative data underwent thematic analysis with triangulation across multiple sources. Participants demonstrated substantial improvement in questioning skills, with overall mean scores progressing from 1.55 (baseline) to 3.24 (post-intervention), representing a 109% increase. The most significant improvements occurred in question type diversity (275% increase), question quality (200% increase), and independence in question formulation (216.7% increase). Performance classifications advanced from